2004
DOI: 10.1038/sj.bjc.6601535
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MTA1 promotes motility and invasiveness of PANC-1 pancreatic carcinoma cells

Abstract: The human metastasis-associated protein 1 (MTA1) is a constituent of the nucleosome-remodelling and -deacetylation complex. Its expression has been correlated with the invasion and metastasis of epithelial neoplasms. To address the functional consequences of MTA1 expression in pancreatic carcinoma cells, we have established PANC-1 pancreatic carcinoma cells that stably express MTA1 as an enhanced green fluorescent fusion protein (EGFP -MTA1). Here, we demonstrate that heterologous expression of EGFP -MTA1 mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 43 publications
0
32
1
1
Order By: Relevance
“…Although MTA1 has been reported to be associated with tumor cell migration, metastasis, and invasiveness in vitro, it is still inconclusive in human. [11][12][13] In this study, we demonstrated that MTA1 overexpression in HCC may contribute to the extrahepatic metastasis as well as vascular invasion. Taken together, it suggests that MTA1 may be in the middle of mechanisms associated with distant metastasis through vascular invasion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although MTA1 has been reported to be associated with tumor cell migration, metastasis, and invasiveness in vitro, it is still inconclusive in human. [11][12][13] In this study, we demonstrated that MTA1 overexpression in HCC may contribute to the extrahepatic metastasis as well as vascular invasion. Taken together, it suggests that MTA1 may be in the middle of mechanisms associated with distant metastasis through vascular invasion.…”
Section: Discussionmentioning
confidence: 94%
“…Among them, the recently identified metastatic tumor antigen 1 (MTA1) is known to increase the migration and invasion of various tumor cells in vitro. [11][12][13] MTA1 has also been suggested to play a role in angiogenic processes as a stabilizer of hypoxiainducible factor 1␣ (HIF1␣). [14][15][16] Thus, it has been reported that MTA1 overexpression is closely correlated with an aggressive course in several human cancers, such as breast, prostate, colorectal, gastric, and esophageal cancers.…”
mentioning
confidence: 99%
“…Overexpression of MTA1 results in increased anchorageindependent growth and growth of tumor xenografts in breast and pancreatic cancer cells (11,12). Although MTA1 is a part of the NuRD complex and associated with HDACs, its precise function as a corepressor remained speculative until recently, when MTA1 was found to act as a repressor for ligand-induced estrogen receptor (ER) transactivation in breast cancer cells (12).…”
mentioning
confidence: 99%
“…In similar studies, DNA microarray analysis was used to investigate MTA1 expression in 300 patient samples comprising of metastatic prostrate cancer, clinically localized prostrate cancer and benign prostrate tissue, MTA1 expression was correlated positively with malignant potential [24]. Human laryngeal squamous cell carcinomas, lung cancers, ovarian carcinomas, hepatocellular carcinomas and breast cancers also demonstrate MTA1 to be associated with tumor aggression [21,45,53,59,69].…”
Section: Mta1-a Potentially Novel Metastasis Associated Antigen For Imentioning
confidence: 99%